Autogenic Relaxation on Anxiety Among Pregnant Women at Trimulyo Community Health Center, East Lampung - Wulandari, Lusia Asih; Retno, Sri Nowo (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Anxiety in pregnancy is commonly the result of certain concerns regading the health condition of the fetus and the delivery process. It is estimated that 10% to 55.7% of pregnant women experience mild to severe anxiety. Autogenic relaxation is one type of non-pharmacological therapy to relieve anxiety symptoms. The current study aims to find out the effect of autogenic relaxation on the anxiety among pregnant women in the work area of Trimulyo CHC, East Lampung Regency. This was a quasi-experimental study with a non-randomized control group pretest-postest design. The populations were pregnant women in the third trimester. 20 samples were assigend into the intervention group and the control group, which involved 10 pregnant women, respectively. Anxiety was assessed based on Pregnancy Related Anxiety Questionere-Revision2 (PRAQ-R2). The results from paired t-test presented that the mean anxiety before autogenic relaxation in the intervention and control group was 36.10±4.581 and 35.80±4.709, respectively. After autogenic relaxation, the mean anxiety was 24.00±2.108 and 35.90±4.067, respectively. It was found a significant difference in the mean anxiety after treatment between the two groups (p-value=0.000) by -11.90±1.449. Thus, autogenic relaxation had an effect on the anxiety among pregnant women. Autogenic relaxation application as non-pharmacological therapy is recommended to relieve anxiety in pregnant women.